Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Intervening - Agustina Dian Putri Manurung (Penerbit Goodwood, 2022)
Purpose: This research was conducted to find out and explain several factors that are thought to influence firm value, such as how good corporate governance is and how the company's financial performance is. Research Methodology: The research sample was taken based on several criteria while the data collection was based on a documentation study which was processed using SPSS and the Sobel Test. Results: This study shows that financial performance cannot mediate the effect of managerial ownership on the value of a company. However, financial performance can mediate the effect of institutional ownership on the value of a company. Limitations: The number of variables selected in this study is limited, as well as the number of samples studied. Contribution: It is hoped that this research can be used as reference material for those who wish to do further research on this topic and is expected to be useful for company managers in an effort to maximize company value as their main objective.